A summer residence, Port of Spain, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2011)
A picture of people sailing in the bay in front of a summer house situated just off the shoreline.
Colour: Coloured; Style: Landscape; Other:U nbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Boats and boating; Bays--Trinidad and Tobago